Effectiveness of hydrogen peroxide treatments in preventing biofilm clogging in drip irrigation systems applying treated wastewater. Issue 6 (3rd July 2022) - Japhet, Nathan; Tarchitzky, Jorge; Chen, Yona
Abstract: The application of treated wastewater (TWW) via pressurized drip irrigation (DI) systems, specifically micro-irrigation, is an effective solution to mitigate water scarcity. TWW contains a higher concentration of nutrients and microbial activity compared to fresh water (FW) and poses a larger danger of fouling and subsequent clogging to DI systems. The goal of this paper was to characterize the effectiveness of chemical treatments, specifically hydrogen peroxide (H2 O2 ) in preventing clogging in DI systems utilizing secondary (ST) and tertiary (TT)_TWW. A novel field model was employed to compare the flow rate (FR), fouling accumulation and composition in laterals and emitters of different treatments. Under ST_TWW irrigation, control treatment performance quickly declined while regular low concentration H2 O2 treatments exhibited the lowest amounts of fouling and maintained nominal FR and coefficient of variation (CV). Shock treatments, defined as periodical applications of concentrated chemicals combined with lateral flushing, were ineffective in maintaining satisfactory irrigation performance.